CLINICAL CHARACTERISTICS AND COMORBIDITIES OF VERY ELDERLY PATIENTS WITH HYPERTENSION AND CHRONIC KIDNEY DISEASE. (June 2018) - Staiculescu, R.; Fronea, M.; Dediu, G.; Olteanu, D.; Balaceanu, B.; Gurau, D.; Balaceanu, A.
Abstract : Objective: The aim of the study was to assess the characteristics and cardiovascular risk in hospitalised very elderly patients with hypertension and chronic kidney disease. Design and method: The retrospective study included 52 patients with high blood pressure admitted to Clincal Emergency Hospital between January 2014 - May 2017. Results: The average age was 95 years, with a minimum age of 90 years and a maximum age of 98 years. Gender distribution: 69.23% women and 30.76% men. The following distribution in patients with high blood pressure was observed: grade I 9.6%, grade II 63.4%, grade III 25%. One patient had secundary hypertension asociated with renal parenchymal disease. Comorbidities: chronic kidney disease evaluated by MDRD equation was encountered in 98% of cases, with the following staging: G2 28.8%, G3a 32.6%, G3b 24%, G4 9.6% and G5 28.8%. The average level of creatinine at admission was 1.46 and at discharge was 1.34. Worsening of renal function was noticed in 9.6% of patients. At 63.46% of patients, nonspecific inflammatory syndrome was identified, with a mean erythrocyte sedimentation rate of 55 and a mean fibrinogen level of 639. Urinary tract infection has been proven in 26.92% of cases. Identified germs were E. Coli in 71.42% cases of infections, Enterococcus, Klebsiella, Proteus and Pseudomonas in 7.14% of each cases. At admission 25% of patients had acidosis and 5.7% alkalosis, hyponatremia was found in 15.3% of cases, hypernatremia in 3.8%, hypokalemia in 32.6% and hyperkalemia in 3.8%. Hyperuricemia was found in 23% of cases. 69% of patients had systemic atherosclerosis and 21% have had a stroke. During hospitalization, 46.15% of patients received treatment with beta blockers, calcium channel blockers were used in 30.76% of cases, diuretics in 63.46%, angiotensin converting enzyme inhibitors in 26.92% and antibiotics in 69.23% of cases. Conclusions: Hypertension is a significant risk factor for kidney disease in the elderly population and special attention should be paid on medication and the doses of drugs that are used to treat these patients.